A generalized model for quantitative evaluation of reliability indices of the national grid system (2010)
Reliability indices are considered to be reasonable and logic ways to judge the performance of an electric power system. Reliability indices which are proposed by the IEEE are used to evaluate the performance of selected distribution systems on the national grid. Ten years of outage data (1998 - 2007) from seven selected distribution systems on the national grid were used as case studies in this research work. A generalized model is developed for a quantitative evaluation of relative indices of the national grid system. The development of the model stated with identification of the system reliability indices and estimating the contributions of system indices to the failure rate of the selected distribution system on the national grid. The computed system reliability indices are used as input parameters for the generalized model. Relative CAIDI index is computed by simulation using MATLAB 7.7 which automatically generates the graph of the relative CAIDl against names of feeders. The percentage average relative CAIDls for Ibadan, Port-Harcourt and Benin distribution systems are 71.86%, 52.79% and 75.79% respectively, thus, average reliability levels. Ilorin, Ikeja, Kaduna and Kano distribution systems have percentage average relative CAIDls of 11.95%, 39.76%, 40.17% and 41.08% respectively with poor reliability levels. With the aid of curve fitting (cf) tools, two distinct model equations were developed from which a generalized model is formulated for a quantitative evaluation of reliability indices of the national grid. The generalized model is a polynomial function whose order depends majorly on the level of industrialization of the distribution systems and the number of distribution feeders.